Cardiovascular-Specific Mortality and Kidney Disease in Patients Undergoing Vascular Surgery - Huber, Matthew (JAMA Surg, 2016)
IMPORTANCE: Acute kidney injury (AKI) affects as many as 40% of patients undergoing surgery and is associated with increased all-cause mortality. Chronic kidney disease (CKD) is a well-known risk factor for cardiovascular mortality. OBJECTIVE: To determine the association between kidney disease and long-term cardiovascular-specific mortality after vascular surgery. DESIGN, SETTING, AND PARTICIPANTS: A single-center cohort of 3646 patients underwent inpatient vascular surgery from January 1, 2000, to November 30, 2010, at a tertiary care teaching hospital. To determine cause-specific mortality for patients undergoing vascular surgery, a proportional subdistribution hazards regression analysis was used to model long-term cardiovascular-specific mortality while treating any other cause of death as a competing risk. Kidney disease constituted the main covariate after adjusting for baseline patient characteristics, surgery type, and admission hemoglobin level. Final follow-up was completed July 2014 to assess survival through January 31, 2014, and data were analyzed from June 1, 2014, to September 7, 2015. MAIN OUTCOMES AND MEASURES: Perioperative AKI, presence of CKD, and overall and cause-specific mortality. RESULTS: Among the 3646 patients undergoing vascular surgery, perioperative AKI occurred in 1801 (49.4%) and CKD was present in 496 (13.6%). The top 2 causes among the 1577 deaths in our cohort were cardiovascular disease (845 of 1577 [53.6%]) and cancer (173 of 1577 [11.0%]). Adjusted cardiovascular mortality estimates at 10 years were 17%, 31%, 30%, and 41%, respectively, for patients with no kidney disease, AKI without CKD, CKD without AKI, and AKI with CKD. Adjusted hazard ratios (95%CIs) for cardiovascular mortality were significantly elevated among patients with AKI without CKD (2.07 [1.74–2.45]), CKD without AKI (2.01 [1.46–2.78]), and AKI with CKD (2.99 [2.37–3.78]) and were higher than those for other risk factors, including increasing age (1.03 per 1-year increase; 1.02–1.04), emergent surgery (1.47; 1.27–1.71), and admission hemoglobin levels lower than 10 g/dL (1.39; 1.14–1.69) compared with a hemoglobin level of 12 g/dL or higher. CONCLUSIONS AND RELEVANCE: Perioperative AKI is common in patients undergoing vascular surgery and is associated with a high risk for cardiovascular-specific mortality comparable to that seen with CKD. These findings reinforce the importance of preoperative and postoperative risk stratification for kidney disease and the implementation of strategies now available to help prevent perioperative AKI.